Green preparation of carbon quantum dots with wolfberry as on-off-on nanosensors for the detection of Fe3+ and l-ascorbic acid. (15th May 2022) - Gu, Lin; Zhang, Jingru; Yang, Guangxin; Tang, Yunyu; Zhang, Xuan; Huang, Xuanyun; Zhai, Wenlei; Fodjo, Essy Kouadio; Kong, Cong
Highlights: A facile and green hydrothermal approach for the preparation of nitrogen-doped carbon quantum dots ( N -CQDs) with wolfberry is proposed. The N -CQDs displayed superior fluorescence characteristics of CQDs with a quantum yield up to 22%. This N -CQDs is successfully developed for 'on-off' detection of Fe 3+ and 'on-off-on' detection of l -ascorbic acid. Abstract: A green and facile hydrothermal synthesis approach is proposed for the preparation of nitrogen-doped carbon quantum dots ( N -CQDs) with wolfberry. These N -CQDs were developed as a highly sensitive fluorescent 'on-off-on' switch sensor for the sensing of Fe 3+ and l -ascorbic acid (AA). The N -CQDs displayed superior fluorescence characteristics of CQDs with a quantum yield up to 22%. The N -CQDs were demonstrated to selectively react with Fe 3+, leading to fluorescence quenching effect, which was successfully used for the detection of Fe 3+ with a limit of detection at 3 μmoLL −1 . The addition of AA is supposed to repair the surface defects, and result in the fluorescence recovery. Based on this effect, the strategy of 'on-off-on' detection of AA was established with a limit of detection at 1.8 μmoLL −1 . Furthermore, the practical application of the detection of Fe 3+ lake water and AA in medical tablet was demonstrated, promising an effective and efficient 'on-off-on' nanosensor with low-cost, green synthesis for Fe 3+ and AA detection.